Effect of mass sports activity on prosocial behavior: A sequential mediation model of flow trait and subjective wellbeing - Xiyan Duan; Xiaohua Wang; Xiaogang Li; Shichen Li; Yiping Zhong; Te Bu (Frontiers in Public Health, 2022)
ObjectivesParticipation in mass sports is one of the most efficient strategies for people to attain physical and mental health in China. Prosocial behavior has a positive effect on social development. This study developed a conceptual model with mass sports activity as the independent variable, prosocial behavior as the dependent variable, and flow trait and subjective wellbeing as the mediating variables.MethodsParticipants (N = 351) completed an online survey. Mass sports activity, flow trait, subjective wellbeing, and prosocial behavior were measured using the physical activity rank scale-3 (PARS-3), short dispositional flow scale (SDFS), index of wellbeing (IWB), and prosocial tendencies measure (PTM), respectively. Descriptive statistics compared differences between sports population (PARS-3, ≥ 36) and non-sports population (PARS-3, <36). Mediation effect was analyzed using the PROCESS (Template, Model 6).ResultsSports population scored significantly higher (all P ≤ 0.05) on SDFS, IWB, and PTM than non-sports population. Participation in mass sports stimulated flow trait and thus improved prosocial behavior, with a mediation effect value of 0.061 (95% CI, 0.028–0.104), which accounted for 30.18% of the total effect. Participation in mass sports enhanced subjective wellbeing and thus improved prosocial behavior, with a mediation effect value of 0.044 (95% CI, 0.007–0.090), which accounted for 21.96% of the total effect. Flow trait and subjective wellbeing mediated the relationship between mass sports activity and prosocial behavior in a sequential manner, with a mediation effect value of 0.059 (95% CI, 0.035–0.090), which accounted for 29.23% of the total effect.ConclusionThe preliminary results of the mediation model validated the hypothesized sequential links between mass sports activity, flow trait, subjective wellbeing, and prosocial behavior. Greater participation in mass sports increases the likelihood of prosocial behavior.